Macro Determinants on Non-performing Loans and Stress Testing of Vietnamese Commercial Banks’ Credit Risk - Hà, Võ Thị Ngọc; Triển, Lê Vĩnh; Diệp, Hồ (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 30 No 5E, 2014)
Abstract: This study investigates the relationship between several macroeconomic factors and the nonperforming loan ratio in the Vietnamese banking system by using panel regression models. The study employs a sample of eight listed banks representing approximately 50% of the market share of the banking system operating from the fourth quarter of 2008 to the second quarter of 2013. Consistent with international and domestic evidence, we have found that the GDP growth rate is negatively related to nonperforming loans (NPL) while the lending rate is positively related to NPL. Contrary to other studies, the inflation and exchange rates have not been found statistically significant with nonperforming loans for the Vietnamese commercial banks. The study also employs both a conventional approach and a value-at-risk (VaR) approach to conduct macro stress testing in order to predict the levels of the nonperforming loans and the expected losses that banks could suffer. The forecast result shows that under adverse and stressed scenarios the minimum capital requirement for banks to survive is about 6% at the end of 2014. Implications will then be provided for bankers and policy makers accordingly. Keywords: Nonperforming loans, capital adequacy, stress testing, vector autoregressive model.